Formation of Lung Inducible Bronchus Associated Lymphoid Tissue Is Regulated by Mycobacterium tuberculosis Expressed Determinants - Dunlap, Micah D.; Prince, Oliver A.; Rangel-Moreno, Javier; Thomas, Kimberly A.; Scordo, Julia M.; Torrelles, Jordi B.; Cox, Jeffery; Steyn, Adrie J. C.; Zúñiga, Joaquín; Kaushal, Deepak; Khader, Shabaana A. (Frontiers in Immunology, 2020)
Mycobacterium tuberculosis (Mtb) is the causative agent of the infectious disease tuberculosis (TB), which is a leading cause of death worldwide. Approximately one fourth of the world’s population is infected with Mtb. A major unresolved question is delineating the inducers of protective long-lasting immune response without inducing overt, lung inflammation. Previous studies have shown that the presence of inducible Bronchus-Associated Lymphoid Tissue (iBALT) correlate with protection from Mtb infection. In this study, we hypothesized that specific Mtb factors could influence the formation of iBALT, thus skewing the outcome of TB disease. We infected non-human primates (NHPs) with a transposon mutant library of Mtb, and identified specific Mtb mutants that were over-represented within iBALT-containing granulomas. A major pathway reflected in these mutants was Mtb cell wall lipid transport and metabolism. We mechanistically addressed the function of one such Mtb mutant lacking mycobacteria membrane protein large 7 (MmpL7), which transports phthiocerol dimycocerosate (PDIM) to the mycobacterial outer membrane (MOM). Accordingly, murine aerosol infection with the Mtb mutant Δmmpl7 correlated with increased iBALT-containing granulomas. Our studies showed that the Δmmpl7 mutant lacking PDIMs on the surface overexpressed diacyl trehaloses (DATs) in the cell wall, which altered the cytokine/chemokine production of epithelial and myeloid cells, thus leading to a dampened inflammatory response. Thus, this study describes an Mtb specific factor that participates in the induction of iBALT formation during TB by directly modulating cytokine and chemokine production in host cells.